Pulmonary Hypertension in Pregnancy: Challenges and Solutions - Afify H; Kong A; Bernal J; Elgendy IY (Dove Medical Press, 2022)
Hesham Afify,1,2 Alexander Kong,1,2 Jopher Bernal,1,2 Islam Y Elgendy3 1Department of Internal Medicine, University of Central Florida HCA Healthcare GME, Greater Orlando, FL, USA; 2Department of Internal Medicine, University of Central Florida College of Medicine, Orlando, FL, USA; 3Division of Cardiovascular Medicine, Gill Heart Institute, University of Kentucky, Lexington, KY, USACorrespondence: Islam Y Elgendy, Division of Cardiovascular Medicine, Gill Heart Institute, University of Kentucky, Lexington, KY, USA, Email iyelgendy@gmail.comAbstract: Pulmonary hypertension (PH) is a heterogeneous disease characterized by an elevated mean pulmonary artery pressure of 20 mm Hg or above. PH is a prevalent condition among women of reproductive age and is linked with poor prognosis during pregnancy. Pregnancy is a stressful event and complicates the management and prognosis in patients with PH. In this review, we discuss the pathogenesis, clinical presentation as well as therapeutic options for PH during pregnancy. We also highlight knowledge gaps to guide future research.Keywords: pulmonary hypertension, pulmonary arterial hypertension, pregnancy, women